Medicinal Plants used as Remedies for the Treatment of the Oral Mucosa (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Based on open literature sources, modern requirements for the dosage form of gels have been determined. The characteristics and features of technological production are given. The analysis of the assortment of medicines based on medicinal plant raw materials used in the treatment of the oral mucosa has been carried out.